2019
DOI: 10.1103/physrevlett.122.232501
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Composition Dependent Reactor Antineutrino Yield at RENO

Abstract: We report a fuel-dependent reactor electron antineutrino (νe) yield using six 2.8 GW th reactors in the Hanbit nuclear power plant complex, Yonggwang, Korea. The analysis uses 850 666 νe candidate events with a background fraction of 2.0 % acquired through inverse beta decay (IBD) interactions in the near detector for 1807.9 live days from August 2011 to February 2018. Based on multiple fuel cycles, we observe a fuel 235 U dependent variation of measured IBD yields with a slope of (1.51 ± 0.23) × 10 −43 cm 2 /… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…The spectral measurements indicated a new anomaly ("5-MeV bump") when compared with theoretical calculations, an observation further confirmed by the NEOS Collaboration [18], and by reexamination of earlier reactor antineutrino data [19]. Observation of the evolution of the reactorν e spectrum from commercial reactors [20][21][22][23] and measurement of the 235 Uν e spectrum from highly enriched uranium research reactors [24,25] have also been performed, providing first glimpses at the dependence of spectral features on reactor fuel content. Interpretations of the reactorν e flux and spectrum anomalies reveal the complexes in the fission beta spectrum conversion and nuclear databases [26][27][28][29][30][31][32].…”
mentioning
confidence: 56%
“…The spectral measurements indicated a new anomaly ("5-MeV bump") when compared with theoretical calculations, an observation further confirmed by the NEOS Collaboration [18], and by reexamination of earlier reactor antineutrino data [19]. Observation of the evolution of the reactorν e spectrum from commercial reactors [20][21][22][23] and measurement of the 235 Uν e spectrum from highly enriched uranium research reactors [24,25] have also been performed, providing first glimpses at the dependence of spectral features on reactor fuel content. Interpretations of the reactorν e flux and spectrum anomalies reveal the complexes in the fission beta spectrum conversion and nuclear databases [26][27][28][29][30][31][32].…”
mentioning
confidence: 56%
“…The Rate Anomaly: We begin with combined analyses of the inverse beta decay (IBD) event rates measured at the short-baseline experiments at Bugey [35,36], Gösgen [37], ILL [38,39], Krasnoyarsk [40][41][42], Nucifer [43], Savannah River [44] and Rovno [45,46]. Additionally, we analyze Chooz [47], Double Chooz [34] and Palo Verde [48,49] at medium baselines, as well as fuel evolution results from Daya Bay [50] and RENO [51,52]. We highlight the salient features of our analysis here; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, in Ref. [25], the RENO collaboration showed that the relative amplitude of the 5 MeV bump is correlated with the amount of 235 U in their nuclear reactor. These results again shed doubt on the validity of the theoretical flux calculations for this isotope.…”
Section: Or Nuclear Physics Miscalculations?mentioning
confidence: 99%
“…Despite the evidences presented in the previous section, there are also experimental results that support flux miscalculations as the origin of the reactor antineutrino anomaly. In more detail, both the Daya Bay [24] and RENO [25] experiments were able to monitor the abundance of the two most common β-decaying isotopes in their nuclear reactors: 239 Pu and 235 U. Therefore, they could disentangle whether the observed flux deficit affects both isotopes in the same way -the expected result if it were due to sterile neutrino oscillations -or not.…”
Section: Or Nuclear Physics Miscalculations?mentioning
confidence: 99%